2012
DOI: 10.1155/2012/145861
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Next Frontier for Tobacco Control: Nondaily Smoking among New York City Adults

Abstract: Objective. Among current smokers, the proportion of Nondaily smokers is increasing. A better understanding of the characteristics and smoking behaviors of Nondaily smokers is needed. Methods. We analyzed data from the New York City (NYC) Community Health Survey to explore Nondaily smoking among NYC adults. Univariate analyses assessed changes in Nondaily smoking over time (2002–2010) and identified unique characteristics of Nondaily smokers; multivariable logistic regression analysis identified correlates of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…This proportion is similar to that seen at the NYC population-level (Sacks et al, 2012), but higher than the proportion at the national level (Centers for Disease Control and Prevention (CDC), 2011). We also found that non-daily smokers were more likely to quit smoking than daily smokers.…”
Section: Discussionsupporting
confidence: 65%
“…This proportion is similar to that seen at the NYC population-level (Sacks et al, 2012), but higher than the proportion at the national level (Centers for Disease Control and Prevention (CDC), 2011). We also found that non-daily smokers were more likely to quit smoking than daily smokers.…”
Section: Discussionsupporting
confidence: 65%
“…A similar pattern is seen in New York City (NYC); from 2002 to 2010, NYC's adult smoking prevalence declined from 22% to 14%, while the proportion of light daily smokers increased from 31% to 37% and non-daily smokers increased from 31% to 36% 2. Jurisdictions other than the USA have also begun to focus on light and non-daily smokers as populations needing examination and programming, in part, due to their growing contributions to s moking prevalence 3–5…”
Section: Introductionsupporting
confidence: 53%
“…1,5 In comparison with heavier smokers, they tend to have higher socioeconomic status (SES) 5 ; self-identify as nonsmokers 1,7 ; show fewer signs of nicotine dependence 1,5 ; and be more motivated to quit smoking. 2,5,7 There is a need for increased understanding of nondaily and lowrate daily smokers and their quitting beliefs and behavior, and in particular for longitudinal studies. 5 Most existing longitudinal studies are short-term, with follow-up ranging from 6 months to 7 years.…”
mentioning
confidence: 99%